Legal Protection Against Photographers Whose Works are Uploaded to Instagram Social Media Without Permission - Suhartini Suhartini; Dian Eka Pebriani (RESAM Jurnal Hukum, 2023)
The Narcotics Unit of the Central Aceh Resort Police revealed 9 (nine) drug cases handled by his party, of which 3 (three) of the 9 (nine) suspects were known to be underage. The law on the criminal justice system for children requires every law enforcement officer to carry out diversification of cases of criminal acts committed by children. The purpose of this research is to find out the process of investigating children as perpetrators of narcotics crimes and to find out the problems of investigators in applying diversion to children as perpetrators of narcotics crimes. This research is a normative juridical research using a case approach and laws and regulations. The results of this study explain that the process of investigating children as perpetrators of narcotics crimes uses methods that have been regulated in the regulations of the juvenile justice system. Problems with investigators in the application of diversion, investigators consider that narcotics crimes carry a penalty of more than 7 years, so that the application of diversion against children who commit narcotics crimes cannot be carried out, and there are no guidelines (SOP) from the National Police leadership in terms of diversion so that investigators only rely on juvenile justice system law.